Industasis, a promotion of tumor formation by nontumorigenic stray cells - Pajer, Petr; Karafiát, Vít; Pecenka, Vladimír; Pruková, Dana; Dudlová, Jana; Plachy, Jirí; Kasparová, Petra; Dvorák, Michal (Cancer research, 2009)
A tumor cell is formed when a critical amount of endogenous and/or exogenous tumorigenic stimuli is exceeded. We have shown that the transient presence of nontumorigenic stray cells in tissues of experimental animals that contain cells with a subcritical set of genetic mutations can act as a tumor-promoting stimulus. To induce somatic mutations in all chicken tissues, we have used the MAV-2 retroviral insertion system that almost exclusively generates nephroblastomas. MAV-2 mutagenized animals i.v. inoculated with nonmalignant cells developed early clonal lung tumors before nephroblastomas. Importantly, the injected cells did not become a component of resultant tumors. Lung tumors displayed specific mutational signature characterized by an insertion of MAV-2 provirus into the fyn-related kinase (frk) promoter that results in the overexpression of the frk gene. In contrast, plag1, foxP, and twist genes were most often mutagenized in nephroblastomas. Based on such observations, we propose the mechanism termed industasis, a promotion of fully malignant phenotype of incipient tumor cell by stray cells, and hypothesize that it might be the underlying cause of human multiple primary tumors.
Keywords: kur domácí; nádorová transformace buněk; nádory ledvin; nádory plic; Chickens; Cells; Lung Neoplasms; fyziologie virů; Wilms Tumor; Cell Transformation, Neoplastic; Neoplasm Invasiveness; Kidney Neoplasms; mnohočetné primární nádory; Models, Biological; Cell Movement; kultivované buňky; Neoplasms, Multiple Primary; Animals; biologické modely; kuřecí embryo; proviry; inzerční mutageneze; zvířata; invazivní růst nádoru; pohyb buněk; Virus Physiological Phenomena; Cells, Cultured; Wilmsův nádor; Proviruses; Mutagenesis, Insertional; buňky; Chick Embryo